The effect of product development and commercialization on competitive advantage - Muhammad Haikal, Amirol Lai (2016)
The aim of this research is to examine and identify the effect of product development and commercialization (both strategic and operational sub processes) on competitive advantage. Strategic product development and commercialization, and, operational product development and commercialization is set as the independent variables. Meanwhile, organization’s competitive advantage is classified as the dependent variable. One hundred sixty two respondents from Kentucky Fried Chicken (KFC) Malaysia Holding were surveyed by questionnaire. The collected data is analysed by using reliability tests, normality tests, descriptive statistics, correlation analysis and regression analysis. Results show that there is significant positive effects of product development and commercialization (both strategic and operational sub processes) on KFC’s competitive advantage.